2020
DOI: 10.1111/nyas.14477
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS‐CoV‐2 through breast milk and breastfeeding: a living systematic review

Abstract: The pandemic of coronavirus disease 2019 (COVID-19) is caused by infection with a novel coronavirus strain, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). At present, there is limited information on potential transmission of the infection from mother to child, particularly through breast milk and breastfeeding. Here, we provide a living systematic review to capture information that might necessitate changes in the guidance on breast milk and breastfeeding given the uncertainty in this area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 302 publications
(296 reference statements)
3
137
0
15
Order By: Relevance
“…To ensure that current evidence and updated information are available to the research communities and final users, a living systematic review will be conducted using rapidly emerging and new research evidence generated through a continual literature search approach as previously described elsewhere 25 . Standard method of reporting living systematic reviews 26 were used and will be used every time when the new COVID‐19 research evidence become available.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that current evidence and updated information are available to the research communities and final users, a living systematic review will be conducted using rapidly emerging and new research evidence generated through a continual literature search approach as previously described elsewhere 25 . Standard method of reporting living systematic reviews 26 were used and will be used every time when the new COVID‐19 research evidence become available.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] While in utero vertical transmission remains unproven, 7 8 10 there may be some indication of transplacental passage of the virus. 11 Currently there is no evidence of viable, infective SARS-Co-V-2 in human milk, [12][13][14] while there are increasing reports of SARS-Co-V-2 specific immunoglobulin in infected mother's milk. [14][15][16] Isolating infants from their mothers with COVID-19 and prohibiting breastfeeding has not been associated with less postpartum transmission of the virus than where mothers are permitted to breastfeed while using appropriate infection prevention and control (IPC) measures (masks, handwashing, World Health Organization, pp 42-43).…”
Section: Introductionmentioning
confidence: 99%
“…The Center for Disease Control and Prevention and the World Health Organization (WHO) recommend breast-feeding for mothers infected with SARS-CoV-2, as the benefits of mother's milk are thought to outweigh potential risks of transmitting the virus to the infant 1,2 . A recent systematic review, reporting on 77 nursing mothers from 37 studies concluded that there was no convincing evidence of transmission of SARS-CoV-2 via breastmilk 3 . As of December 14 th , 2020, the WHO reported over 71 million people infected by SARS-CoV-2 globally, and over 1.5 million deaths.…”
Section: Introductionmentioning
confidence: 99%